Assessment of efficiency of agricultural enterprise management: methods and trend analysis - Yakubiv, Valentyna; Yakubiv, Roman; Maksymiv, Yuliia; Hryhoruk, Iryna; Popadynets, Nazariy; Iwaszczuk, Natalia (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
The paper analyzes various scientific approaches to assessing the effectiveness of enterprise management. The advantages and disadvantages of using the four most common methods of assessing the effectiveness of enterprises are substantiated, such as 1) comprehensive assessment based on the methods of economic analysis; 2) analysis based on experimental estimates; 3) using the scoring method; 4) assessment based on testing. Given the fact that currently there is no single approach to assessing the effectiveness of enterprise management, including agricultural enterprises, the article proposes the author's method of assessing the effectiveness of management in agricultural enterprises. This methodology assumes that the effectiveness of management in agricultural enterprises is determined by integrating three indicators: economic efficiency of management, social efficiency of management, and organizational efficiency of management. The proposed methodology includes the gradual integration of partial 19 indicators in terms of economic, social, and organizational efficiency. Analysis of this phenomenon was conducted based on agricultural enterprises of the Ivano-Frankivsk region aimed at testing the developed methodology for assessing the effectiveness of management. The paper presents the research of the influence of the number of employees on the level of management efficiency in agricultural enterprises, the influence of enterprise size (by land area) on the level of management efficiency in agricultural enterprises, and the influence of average employment per 100 hectares of agricultural land on the level of agricultural management. The research was done using the grouping method. According to the results of the study, it was established that the developed methods for assessing the effectiveness of the management of agricultural enterprises can be used in practice.